THE ROLE OF DIGITAL PLATFORMS IN DEVELOPING INDEPENDENT LEARNING COMPETENCE AMONG STUDENTS - Mamatova Umida Zafarjon qizi (Bright Mind Publishing, 2025)
This article highlights the issue of students' formation of independent educational competence through the use of digital educational platforms. It analyzes the need for independent learning, the importance of digital tools in today's learning environment, and their impact on learning effectiveness. It also shows ways for students to develop competencies such as critical thinking, independent information analysis, and self-control. At the end of the article, recommendations are given on how to improve the digital educational environment, as well as the results obtained based on experience.
Keywords: Independent learning, digital platforms, improving the educational environment, student competence, digital literacy, adaptive learning, multimedia resources, cross-platform integration, digital monitoring, online learning, interactive educational tools.